MerTK negatively regulates Staphylococcus aureus induced inflammatory response via Toll-like receptor signaling in the mammary gland. (June 2020) - Zahoor, Arshad; Yang, Yaping; Yang, Chao; Khan, Sher Bahadar; Reix, Christine; Anwar, Farhan; Guo, Meng-yao; Deng, Ganzhen
Graphical abstract: Highlights: Activation of MerTK signaling negatively regulates TLR2, TLR6 signaling network via the SOCS1/SOCS3 proteins by targeting TRAF6. MerTK inhibits the S. aureus induced NF-κB and MAPKs signaling pathways both in-vivo & in-vitro when compared with MerTK −/− . MerTK via intrinsic feedback downregulate pro-inflammatory cytokines level and inhibits p-IκBα and p-p65 expressions in S. aureus induced mastitis. Intrinsic MerTK negative feedback to inflammation inhibits the TLR2/TLR6 mediated inflammatory responses in mammary gland. Abstract: Mastitis is the most commonly diagnosed infectious disease reducing milk yield and quality and is accompanied by mammary tissue damage in both humans and animals. Mastitis incurs welfare and economic costs as well as environmental concerns regarding treatment. Staphylococcus aureus ( S. aureus ) is a prevalent Gram-positive bacteria and a major cause of mastitis, however, pathogenesis of the intrinsic anti-inflammatory response in mammary tissues is still principally unknown. Our aim, in combatting the S. aureus induced inflammatory response in mammary tissues, was to elucidate the intrinsic anti-inflammatory role of MerTK signaling. Here, we demonstrate that Mer receptor tyrosine kinase (MerTK) regulates an intrinsic negative feedback to balance the over-reaction of the host defense system. S. aureus elicits toll-like receptors 2 and 6 (TLR2/TLR6) signaling pathways, subsequently recruiting TRAF6, whose ubiquitination is intricate to the downstream signaling including MAPKs and NF-κB. We observed that TLR2/TLR6 activation, in response to S. aureus, was concomitant with induced MerTK activation, leading to raised expression of suppressor of cytokine signaling 1 and 3 (SOCS1, SOCS3) in wild type mice mammary tissues and epithelial cells. Meanwhile, S. aureus infection in MerTK −/− mice showed significant increased phosphorylation of p65, IκBα, p38, JNK and ERK along with production of pro-inflammatory cytokines. Moreover, MerTK −/− evidently inhibited S. aureus induced phosphorylation of STAT1 and subsequent SOCS1/SOCS3 expression which are pivotal in the negative feedback mechanism for targeting TRAF6 to inhibit the TLR2/TLR6 mediated immune response. Taken together, our findings demonstrate the importance of MerTK in the regulation of the intrinsic feedback during the inflammatory response induced by S. aureus through STAT1/SOCS1/SOCS3 in mice mammary tissues and mice mammary epithelial cells (MMECs).